An investigation into the perceived value of the College of Radiographers voluntary accreditation scheme for advanced and consultant practitioners in breast imaging. Issue 3 (August 2019) - Deane, L.; Robinson, L.; England, A.
Abstract: Introduction: A voluntary accreditation scheme has been introduced, requiring advanced (AdP) and consultant practitioners (CP) to submit several pieces of work to the College of Radiographers (CoR). However, few individuals have opted to become voluntary accredited. This study investigated the reasons behind becoming voluntary accredited, the value that was gained and why there appears to be a lack of support for the scheme. Methods: An online electronic survey was conducted using a mixed methods approach. Open questions enabled individual opinions and thoughts to be expressed, Likert scale style questions allowed further understanding of the level of agreement and closed questions identified the support for and against the scheme. Results: A total of 55 respondents participated, including 18 AdPs, 25 CPs, 1 consultant trainee practitioner, 5 practitioners and 6 listed as 'other'. Forty-four participants were non-accredited, citing too much clinical work; no recognition from employers and too much effort for little reward. Motivations for joining the scheme were to improve the profession; help create a new consultant post and protect the non-clinical element of the consultant role. Conclusion: The CoR voluntary accreditation scheme has a small perceived value but overall, the majority of respondents believed the scheme did not warrant the work needed to apply. Concern was raised about the risk of creating a two-tier profession by the scheme's instigation. The results of this study suggest that the CoR's voluntary accreditation scheme would need to address these barriers before more practitioners would apply. Highlights: Can protect the non-clinical element of the role. Voluntary accreditation is not recognised beyond scope of radiology department. Requires too much additional work for the little value gained. The expectation of a PhD for consultant radiographers is not supported. Only has a small, perceived value to those accredited.